Therapeutic Antibodies for Myeloid Neoplasms—Current Developments and Future Directions - Schürch, Christian M. (Frontiers in Oncology, 2018)
Therapeutic monoclonal antibodies (mAbs) such as antibody-drug conjugates, ligand-receptor antagonists, immune checkpoint inhibitors and bi-specific T cell engagers have shown impressive efficacy in the treatment of multiple human cancers. Numerous therapeutic mAbs that have been developed for myeloid neoplasms, including acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS), are currently investigated in clinical trials. Because AML and MDS originate from malignantly transformed hematopoietic stem/progenitor cells – so-called leukemic stem cells (LSCs) that are highly resistant to most standard drugs – these malignancies frequently relapse and have a high disease-specific mortality. Therefore, combining standard chemotherapy with anti-leukemic mAbs that specifically target malignant blasts and particularly LSCs or utilizing mAbs that reinforce anti-leukemic host immunity holds great promise for improving patient outcomes. This review provides an overview of therapeutic mAbs for AML and MDS. Antibody targets, the molecular mechanisms of action, the efficacy in pre-clinical leukemia models, and the results of clinical trials are discussed. New developments and future studies of therapeutic mAbs in myeloid neoplasms will advance our understanding of the immunobiology of these diseases and enhance current therapeutic strategies.